Can we trust intuitive jurors? An experimental analysis - Andreas Glöckner; Christoph Engel (Max Planck Institute for Research on Collective Goods, 2008)
Jury members do not normally have the privilege of a complete, unbiased picture of the case. To make the best of patently incomplete evidence, they cannot but at least partially rely on their intuition. We provide evidence for this claim based on self-report data as well as more subtle measures of unconscious modifications of the evidence in order to fit the favoured interpretation (coherence shifts). In three experiments we investigated whether members of a mock jury apply standards of proof in a normatively appropriate way, how well they take into account explicitly stated probability information, and which factors influence the size of coherence shifts. We found a mixed pattern of results: manipulation of the standard of proof influences conviction rates in the intended direction, but there are fewer convictions in both standard of proof conditions than normatively expected. When asked to indicate the minimum probability of guilt necessary for conviction, subjects do not sufficiently discriminate between beyond a reasonable doubt and preponderance of the evidence. Even substantial manipulations of the posterior probability of guilt had very little effect on conviction rates. Reliance on intuitive processes seems to reduce the influence of explicitly stated probabilities. We furthermore found effects of verdict and of the probability manipulation on the size of coherence shifts. We argue that the performance of jury members could be improved by providing them with supplementary information on context, such that they are able to put explicit information on probabilities in perspective.
Keywords: 340; Gerichtsbarkeit; Verhaltensökonomik; Emotion; Test